2004
DOI: 10.1088/0953-2048/17/6/010
|View full text |Cite
|
Sign up to set email alerts
|

The ordering of spontaneous magnetization moments in large-scale two-dimensional superconducting  -ring arrays

Abstract: Large planar arrays of Josephson junctions form two-dimensional systems with many interesting properties, especially arrays containing superconducting π-junctions with unconventional superconducting d-wave symmetry. Here we present an analytical investigation of spontaneous magnetization in two-dimensional superconducting π-ring arrays, starting from an ansatz that each of the identical π-rings carries a magnetic flux with the same frustration index. Our results show that the flux structure with full antiparal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Moreover, we indicated that a 1D π ring chain and 2D π ring arrays will spontaneously magnetize to an 'antiferromagnetic' configuration in the absence of an external magnetic field. Tian et al [7,8] gave the same result after computing a large dimensional model of 1D π ring chains and 2D π ring arrays. This is in accordance with the scanning SQUID observations of the spontaneous magnetization with YBCO-Nb edge junction 1D chains and 2D arrays by Hilgenkemp et al [9], in which they definitely exhibit the 'antiferromagnetic' configuration.…”
Section: Introductionmentioning
confidence: 66%
“…Moreover, we indicated that a 1D π ring chain and 2D π ring arrays will spontaneously magnetize to an 'antiferromagnetic' configuration in the absence of an external magnetic field. Tian et al [7,8] gave the same result after computing a large dimensional model of 1D π ring chains and 2D π ring arrays. This is in accordance with the scanning SQUID observations of the spontaneous magnetization with YBCO-Nb edge junction 1D chains and 2D arrays by Hilgenkemp et al [9], in which they definitely exhibit the 'antiferromagnetic' configuration.…”
Section: Introductionmentioning
confidence: 66%
“…[11−14] Recently, Hilgenkamp et al have reported the realization of large-scale coupled π-loop arrays based on YBa 2 Cu 3 O 7 -Au-Nb Josephson contacts. [15,16] Their experimental results as well as the analysis given by other authors [8,17,18] showed a robust antiferromagnetic ordering of spontaneous magnetization in both square and triangular π-loop arrays and predominant anti-ferromagnetic nearest-neighbour coupling of half-flux quanta in hexagonal π-loop arrays in the absence of an external field. Very recently, the free energy densities in possible flux states of twodimensional square π-loop arrays in an external magnetic field were given analytically and compared numerically by Li et al [19] To complete the theory, in this paper an analytical treatment for the comparison of the free energy densities is provided with the same model described in Refs.…”
Section: Introductionmentioning
confidence: 76%
“…However, in hexagonal π-loop arrays the anti-ferromagnetic state does not exist. [8] Although ferromagnetic states do exist in the neighbourhood of φ e = n + 1/2, the mathematical treatment to provide a flux structure in the vicinity of φ e = n is difficult. The predominant anti-ferromagnetic nearest-neighbour coupling can be described by the bond-order parameter σ, [15,17,21,22] which equals to -1/3 at zero temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations